High-performance lithium ion battery positive electrode material and preparation method thereof

By introducing new doping elements and surface modification materials into the positive electrode materials of lithium-ion batteries, the process and electrolyte formulation are optimized, and the structural phase change and volume expansion problems of the material during charging and discharging are solved, which significantly improves the electrochemical performance of the material. and cycle stability, suitable for high energy density and high magnification applications.

CN119447248AInactive Publication Date: 2025-02-14JIANGXI HONGZHOU VOCATIONAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411586356.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have structural phase change and volume expansion during charging and discharging, poor cycle stability, insufficient electronic conductivity and ion diffusion rate, resulting in poor rate performance and prominent problems in surface side reactions and thermal stability.

Method used

The new doping element combination or doping method is adopted to accurately regulate the electronic structure and crystal structure of the material, introduce surface modification materials to form a stable interface layer, optimize the synthesis process and electrolyte formulation, and improve the electronic conductivity and ion diffusion properties of the material.

Benefits of technology

It significantly improves the specific capacity, cycle stability and rate performance of the positive electrode material of lithium-ion battery, enhances the thermal stability and safety of the material, reduces production costs, and is suitable for application scenarios with high energy density, high magnification and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447248A_ABST
    Figure CN119447248A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion batteries, and discloses a high-performance lithium ion battery positive electrode material and a preparation method thereof, the material has a unique microstructure, a novel doping element combination or doping mode is adopted, an electronic structure and a crystal structure of the material are accurately regulated and controlled, a novel surface modification material is introduced, and a stable interface layer is formed. The preparation method comprises the steps of material synthesis, structural characterization, electrochemical performance testing, surface modification and coating research, research on the influence of ion doping on performance, and research on the compatibility with an electrolyte. The overall performance of the lithium ion battery is improved, so that the lithium ion battery has a wider application prospect in the fields of electric automobiles, energy storage systems and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to but is not limited to the technical field of lithium ion batteries, and in particular relates to a high-performance lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] High-performance cathode materials can significantly improve the specific capacity of lithium-ion batteries, thereby increasing the energy storage density of batteries and meeting the growing demand for long-range mileage for portable electronic devices, electric vehicles, etc. Lithium-ion batteries play a key role in the storage and utilization of renewable energy. The research and development of high-performance cathode materials will help to more effectively integrate renewable energy, reduce dependence on traditional fossil energy, reduce carbon emissions, and promote sustainable development in the energy sector. The research and development of high-performance cathode materials will drive technological progress and innovation in industries such as battery manufacturing, new energy vehicles, and energy storage, creating huge economic value and employment opportunities. Achieving technological breakthroughs in the field of energy storage will help enhance the country's scientific and technological strength and industrial competitiveness in the field of new energy, and occupy a favorable position in the global energy transformation.

[0003] European and American countries have invested heavily in basic research on positive electrode materials for lithium-ion batteries and have achieved a series of important results. For example, the United States has a leading position in the modification and industrialization of ternary materials. Japan has made remarkable achievements in the optimization of traditional positive electrode materials such as lithium cobalt oxide and the research of new lithium-rich manganese-based materials.

[0004] my country has made rapid progress in the research and development and production of cathode materials for lithium-ion batteries. Its output in the fields of ternary materials and lithium iron phosphate has ranked among the top in the world. Domestic scientific research institutions and enterprises have conducted a lot of research work in improving the synthesis process of cathode materials and surface coating modification, and have achieved certain technological breakthroughs.

[0005] In view of the above analysis, the technical problems that need to be solved urgently in the prior art are:

[0006] (1) How to suppress the structural phase change and volume expansion of high specific capacity cathode materials during the charge and discharge process and improve the cycle stability;

[0007] (2) How to improve the electronic conductivity and ion diffusion rate of the cathode material to enhance rate performance;

[0008] (3) How to solve the side reactions and thermal stability problems on the surface of high-nickel ternary materials and improve safety;

[0009] (4) How to select appropriate surface coating and ion doping strategies to improve the overall performance of the material without sacrificing specific capacity;

[0010] (5) How to optimize the electrolyte formula to ensure good compatibility with new cathode materials and reduce interfacial side reactions. Summary of the invention

[0011] In view of the problems existing in the prior art, the present invention provides a high-performance lithium-ion battery positive electrode material and a preparation method thereof.

[0012] The present invention is achieved in this way: a high-performance lithium-ion battery positive electrode material, characterized in that the high-performance lithium-ion battery positive electrode material has a unique microstructure, adopts a new combination of doping elements or doping methods, accurately controls the electronic structure and crystal structure of the material, introduces novel surface modification materials, and forms a stable interface layer.

[0013] Another object of the present invention is to provide a method for preparing a high-performance lithium-ion battery positive electrode material, the method specifically comprising:

[0014] S1: Material synthesis, using a variety of synthesis methods, such as solid phase reaction method, sol-gel method, hydrothermal method, etc., to prepare the target positive electrode material;

[0015] S2: Structural characterization, using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and other methods to characterize the crystal structure, microscopic morphology, element valence state, etc. of the synthesized materials in detail;

[0016] S3: Electrochemical performance test, through constant current charge and discharge test, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and other methods, to evaluate the electrochemical properties of the positive electrode material, such as specific capacity, cycle performance, and rate performance;

[0017] S4: Surface modification and coating research, exploring the effect of surface coating materials (such as carbon layer, oxide layer, etc.) on the stability and electrochemical performance of positive electrode materials, and studying the effects of different coating methods and coating amounts on performance;

[0018] S5: The effect of ion doping on performance. Introduce different ions (such as magnesium, aluminum, titanium, etc.) for doping to improve the electronic conductivity and ion diffusion performance of the material. Study the influence of the type, concentration and distribution of doped ions on the performance of the positive electrode material.

[0019] S6: Compatibility study with electrolyte, examine the electrochemical behavior of cathode materials in different electrolyte systems, optimize electrolyte formulation to improve battery performance, and study the interface reaction mechanism between cathode materials and electrolyte.

[0020] Further, the S1 includes:

[0021] S11: weigh the raw materials according to the stoichiometric ratio and mix them thoroughly;

[0022] S12: According to the selected synthesis method, controlling the reaction conditions (such as temperature, time, atmosphere, etc.) to perform the synthesis reaction;

[0023] S13: washing, drying, grinding and other post-processing of the synthesized product.

[0024] Further, the S2 includes:

[0025] S21: Determine the crystal structure and phase purity of the material using XRD;

[0026] S22: Observe the microstructure and particle size of the material by SEM and TEM;

[0027] S23: Use XPS to analyze the chemical state of elements on the surface of the material.

[0028] Further, the S3 includes:

[0029] S31: preparing positive electrode sheets and assembling them into button cells or soft pack batteries;

[0030] S32: Perform constant current charge and discharge test under a certain voltage range and current density;

[0031] S33: Perform CV and EIS tests to analyze electrode reaction kinetics and interface characteristics.

[0032] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0033] First, the present invention develops one or more lithium-ion battery positive electrode materials with high specific capacity (≥250mAh / g), good cycle stability (capacity retention rate ≥80% after 1000 cycles) and excellent rate performance (capacity retention rate ≥70% at 5C rate).

[0034] The present invention reveals the relationship between the structure and performance of a material and establishes an effective performance control strategy.

[0035] The present invention optimizes the synthesis process of positive electrode materials, reduces production costs, improves production efficiency, and provides technical support for large-scale industrial production.

[0036] The present invention improves the overall performance of lithium-ion batteries, making them have wider application prospects in the fields of electric vehicles, energy storage systems, etc.

[0037] Second, the technical solution of the high-performance lithium-ion battery positive electrode material of the present invention solves the problems of low specific capacity, poor cycle stability, and poor rate performance of existing positive electrode materials in industrial applications. Traditional lithium-ion battery positive electrode materials are prone to volume expansion and structural distortion during the charging and discharging process, resulting in rapid capacity decay and shortened cycle life, especially under high-rate discharge, where performance drops significantly, making it difficult to meet the needs of high-performance batteries. Through the doping and structural optimization of the positive electrode material in the present invention, the electrochemical performance and thermal stability of the material are successfully improved, overcoming the problem of performance degradation of traditional materials when used at high temperatures and high rates.

[0038] The technical solution of the present invention optimizes the electronic structure and crystal structure of the material by doping magnesium, aluminum, titanium and other ions, accurately controlling the doping amount and distribution. This significantly improves the electronic conductivity and ion diffusion performance of the material. The reaction rate of traditional positive electrode materials is limited due to the long ion diffusion path during rapid charging and discharging. The present invention shortens the ion diffusion path by controlling the crystal structure and doping elements, greatly improving the rate performance of the material, so that it still has excellent electrochemical activity under high rate conditions. In addition, doping also improves the stability of the material in high temperature environments and reduces the capacity attenuation under high temperature conditions.

[0039] The present invention adopts synthesis processes such as sol-gel method, solid phase sintering method and coprecipitation method to make the doped ions evenly distributed in the crystal structure, forming a positive electrode material with a porous structure and nanometer particle size. This microstructure design increases the specific surface area of ​​the material and shortens the diffusion path of lithium ions, which helps to improve the specific capacity and energy density of the battery, while improving the volume stability of the material during the charge and discharge process, thereby effectively suppressing the volume expansion problem and improving the cycle stability of the battery. These processes improve production efficiency, reduce material costs, and enhance the practicality of the solution of the present invention.

[0040] In application, the cathode material of the present invention can be applied to a variety of high-performance lithium-ion battery products, including electric vehicles, energy storage power stations and high-power electronic equipment, meeting the needs for high energy density, high rate performance and long cycle life. Especially in the field of electric vehicles, the material of the present invention can improve the battery's endurance and charging speed, while ensuring stability in high temperature environments, further improving the safety and life of the battery.

[0041] In addition, the present invention also achieves the goal of energy conservation and environmental protection in the production process of lithium-ion batteries. By using a low-temperature synthesis process and an efficient waste heat recovery process, energy consumption is reduced, production costs are reduced, and non-toxic and environmentally friendly doping elements are used to avoid potential environmental pollution risks. This makes the present invention not only superior to traditional technologies in performance, but also more green and sustainable in production process, meeting the environmental protection requirements of the current new energy industry.

[0042] The present invention breaks through the performance bottleneck of traditional lithium-ion battery positive electrode materials through doping optimization and microstructure control, significantly improves the capacity, stability and safety of the materials, and makes lithium-ion batteries more competitive in high energy density, high rate and long life application scenarios. Compared with the existing technology, the present invention reduces manufacturing costs and is environmentally friendly while improving material performance, and has significant technological progress and broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a flow chart of a method for preparing a high-performance lithium-ion battery positive electrode material provided by an embodiment of the present invention;

[0044] Figure 2 is a material synthesis flow chart provided by an embodiment of the present invention;

[0045] Figure 3 is a structural characterization flow chart provided by an embodiment of the present invention;

[0046] Figure 4 It is a flow chart of electrochemical performance testing provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] The embodiments of the present invention provide a high-performance lithium-ion battery positive electrode material with a unique microstructure (such as a core-shell structure, a three-dimensional ordered structure, etc.), and adopt a new combination of doping elements or a doping method to accurately control the electronic structure and crystal structure of the material to enhance its electrochemical performance and stability. Novel surface modification materials (such as two-dimensional nanomaterials, metal organic frameworks, etc.) are introduced to form a stable interface layer, inhibit side reactions, and improve cycle life. Its specific capacity is increased by 10% compared to traditional materials, and the cycle stability is also significantly improved.

[0049] The realization of high-performance lithium-ion battery positive electrode materials is achieved through the following key technical means:

[0050] 1. Unique microstructure design:

[0051] By precisely controlling process parameters (such as temperature, time, atmosphere, etc.) during material synthesis, cathode materials with specific crystal structures and particle morphologies are prepared. This microstructure design enables the material to provide a larger surface area and a shorter ion diffusion path, thereby improving its electrochemical reaction rate and specific capacity. In addition, the optimized microstructure can effectively inhibit the volume expansion of the electrode material during the charge and discharge process and enhance the cycle stability of the material.

[0052] 2. New doping element combinations and doping methods:

[0053] During the material preparation process, appropriate metal or non-metal ions (such as magnesium, aluminum, titanium, etc.) are selected for doping. These ions can partially replace the atoms in the positive electrode material and accurately control the electronic structure and crystal structure of the material. By adjusting the type, concentration and distribution of doped ions, the electronic conductivity and ion diffusion properties of the material can be significantly improved, while enhancing the electrochemical performance of the material at high rates. Doping elements can also improve the thermal stability of the material and reduce the capacity decay of the battery at high temperatures.

[0054] 3. Surface modification and coating:

[0055] By introducing novel surface modification materials (such as carbon layer, oxide layer, etc.) on the surface of the positive electrode material, the adverse reaction between the electrode material and the electrolyte can be effectively suppressed to form a stable interface layer. This surface modification not only improves the interface stability of the material, but also enhances the material's cycle performance and rate performance. The surface coating layer can effectively buffer the volume change of the electrode material during the charge and discharge process, reduce the disintegration of the structure, and thus extend the service life of the battery.

[0056] 4. Stability design of the interface layer:

[0057] Through surface modification or doping technology, a stable interface layer can be formed between the positive electrode material and the electrolyte. This interface layer can effectively inhibit side reactions, reduce the loss of active ingredients in the positive electrode material, and reduce the decomposition rate of the electrolyte. The stability of the interface layer is the key to ensuring the long-term cycle performance of the battery, and can significantly reduce the capacity decay of the battery at high voltage.

[0058] In summary, the realization of this high-performance lithium-ion battery positive electrode material significantly improves the electrochemical performance and cycle life of the battery by precisely controlling the material's microstructure, doping element combination, surface modification, and stability of the interface layer.

[0059] like Figure 1 As shown, a method for preparing a high-performance lithium-ion battery positive electrode material provided by an embodiment of the present invention specifically includes:

[0060] S1: Material synthesis, using a variety of synthesis methods, such as solid phase reaction method, sol-gel method, hydrothermal method, etc., to prepare the target positive electrode material;

[0061] S2: Structural characterization, using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and other methods to characterize the crystal structure, microscopic morphology, element valence state, etc. of the synthesized materials in detail;

[0062] S3: Electrochemical performance test, through constant current charge and discharge test, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and other methods, to evaluate the electrochemical properties of the positive electrode material, such as specific capacity, cycle performance, and rate performance.

[0063] S4: Surface modification and coating research, exploring the effect of surface coating materials (such as carbon layer, oxide layer, etc.) on the stability and electrochemical performance of positive electrode materials, and studying the effects of different coating methods and coating amounts on performance;

[0064] S5: The effect of ion doping on performance. Introduce different ions (such as magnesium, aluminum, titanium, etc.) for doping to improve the electronic conductivity and ion diffusion properties of the material, and study the influence of the type, concentration and distribution of doped ions on the performance of the positive electrode material.

[0065] S6: Compatibility study with electrolyte, examine the electrochemical behavior of cathode materials in different electrolyte systems, optimize electrolyte formulation to improve battery performance, and study the interface reaction mechanism between cathode materials and electrolyte.

[0066] like Figure 2 As shown, the S1 includes:

[0067] S11: weigh the raw materials according to the stoichiometric ratio and mix them thoroughly;

[0068] S12: According to the selected synthesis method, controlling the reaction conditions (such as temperature, time, atmosphere, etc.) to perform the synthesis reaction;

[0069] S13: washing, drying, grinding and other post-processing of the synthesized product.

[0070] like Figure 3 As shown, the S2 comprises:

[0071] S21: Determine the crystal structure and phase purity of the material using XRD;

[0072] S22: Observe the microstructure and particle size of the material by SEM and TEM;

[0073] S23: Use XPS to analyze the chemical state of elements on the surface of the material.

[0074] like Figure 4 As shown, the S3 includes:

[0075] S31: preparing positive electrode sheets and assembling them into button cells or soft pack batteries;

[0076] S32: Perform constant current charge and discharge test under a certain voltage range and current density;

[0077] S33: Perform CV and EIS tests to analyze electrode reaction kinetics and interface characteristics.

[0078] The following are two specific embodiments based on the above-mentioned high-performance lithium-ion battery positive electrode material technology:

[0079] Example 1: Preparation and performance optimization of magnesium-doped layered oxide positive electrode materials

[0080] In this embodiment, the prepared positive electrode material is a magnesium-doped layered oxide (such as LiNi0.8Co0.15Al0.05O2, NCA), and its performance is optimized by doping with magnesium ions (Mg2+).

[0081] 1.1 Material synthesis:

[0082] The LiNi0.8Co0.15Mg0.05O2 material was synthesized by the sol-gel method. First, the precursor materials of lithium, nickel, cobalt and magnesium were weighed according to the stoichiometric ratio, dissolved in deionized water, and an appropriate amount of citric acid was added as a chelating agent, and stirred to form a sol. Subsequently, the sol was heated at 200°C until a gel was formed, the gel was pre-burned at 600°C, and then calcined at 800°C for 12 hours to obtain the target positive electrode material.

[0083] 1.2 Structural characterization:

[0084] The crystal structure of the synthesized LiNi0.8Co0.15Mg0.05O2 material was analyzed by X-ray diffraction (XRD), and the results showed that the material had a good layered structure and high phase purity. The microscopic morphology was observed by scanning electron microscopy (SEM), and the particles were evenly distributed and the size was about 2-3 microns.

[0085] 1.3 Electrochemical performance test:

[0086] The synthesized positive electrode material was assembled into a button battery and subjected to constant current charge and discharge tests. The results showed that at a current density of 0.1C, the initial discharge capacity of the material was 185mAh / g, and the capacity retention rate was 92% after 100 cycles. The electrochemical impedance spectroscopy (EIS) test found that the charge transfer impedance of the material was significantly reduced after doping with magnesium ions, which improved the conductivity of the material.

[0087] 1.4 Surface modification:

[0088] In order to further improve the stability of the material, the surface of the material is coated with aluminum oxide (Al2O3). After coating, the cycle stability of the material is significantly improved, and the capacity retention rate can still reach 85% after 500 cycles.

[0089] Example 2: Preparation and performance study of titanium-doped lithium iron phosphate positive electrode material

[0090] In this embodiment, the positive electrode material is titanium-doped lithium iron phosphate (LiFePO 4 ), and the electronic conductivity and ion diffusion of the material are improved by doping with titanium ions (Ti 4 + ).

[0091] 2.1 Material synthesis:

[0092] The LiFe0.98Ti0.02PO4 cathode material was prepared by solid phase reaction method. First, Li2CO3, FePO4 and TiO2 were weighed as precursors according to the stoichiometric ratio and mixed evenly. Then, the mixture was heated to 700℃ and calcined for 10 hours under nitrogen atmosphere to obtain the target material.

[0093] 2.2 Structural characterization:

[0094] X-ray photoelectron spectroscopy (XPS) analysis found that the doped titanium ions were mainly located at the Fe site of the material lattice. The microstructure of the material was observed by transmission electron microscopy (TEM), and the results showed that the crystal structure of the doped material remained intact, and the particle size was relatively uniform, about 100 nanometers.

[0095] 2.3 Electrochemical performance test:

[0096] By assembling into button cells and conducting cyclic voltammetry (CV) tests, the results showed that the initial discharge capacity of titanium-doped LiFePO4 at 1C rate was 150mAh / g, and the capacity retention rate was 95% after 300 cycles. In addition, EIS tests showed that after titanium doping, the ion diffusion impedance of the material was significantly reduced, improving the high-rate charge and discharge performance.

[0097] 2.4 Electrolyte compatibility study:

[0098] Further research on the compatibility of titanium-doped LiFePO4 materials in different electrolytes revealed that the interfacial reaction between the material and LiPF6 solution was relatively stable, which could effectively reduce the internal resistance of the battery and further improve the cycle life and safety performance of the battery.

[0099] These two examples demonstrate the optimization strategy of achieving high-performance lithium-ion battery cathode materials through different doping elements (such as magnesium and titanium) and surface modification methods (such as alumina coating). Each example significantly improves the electrochemical performance and cycle stability of the material by precisely controlling the microstructure and surface characteristics of the material.

[0100] The following are two specific embodiments based on the above-mentioned high-performance lithium-ion battery positive electrode material technology:

[0101] Example 1: Preparation and performance optimization of magnesium-doped layered oxide positive electrode materials

[0102] In this embodiment, the prepared positive electrode material is a magnesium-doped layered oxide (such as LiNi0.8Co0.15Al0.05O2, NCA), and its performance is optimized by doping with magnesium ions (Mg2+).

[0103] 1.1 Material synthesis:

[0104] The LiNi0.8Co0.15Mg0.05O2 material was synthesized by the sol-gel method. First, the precursor materials of lithium, nickel, cobalt and magnesium were weighed according to the stoichiometric ratio, dissolved in deionized water, and an appropriate amount of citric acid was added as a chelating agent, and stirred to form a sol. Subsequently, the sol was heated at 200°C until a gel was formed, the gel was pre-burned at 600°C, and then calcined at 800°C for 12 hours to obtain the target positive electrode material.

[0105] 1.2 Structural characterization:

[0106] The crystal structure of the synthesized LiNi0.8Co0.15Mg0.05O2 material was analyzed by X-ray diffraction (XRD), and the results showed that the material had a good layered structure and high phase purity. The microscopic morphology was observed by scanning electron microscopy (SEM), and the particles were evenly distributed and the size was about 2-3 microns.

[0107] 1.3 Electrochemical performance test:

[0108] The synthesized positive electrode material was assembled into a button battery and subjected to constant current charge and discharge tests. The results showed that at a current density of 0.1C, the initial discharge capacity of the material was 185mAh / g, and the capacity retention rate was 92% after 100 cycles. The electrochemical impedance spectroscopy (EIS) test found that the charge transfer impedance of the material was significantly reduced after doping with magnesium ions, which improved the conductivity of the material.

[0109] 1.4 Surface modification:

[0110] In order to further improve the stability of the material, the surface of the material is coated with aluminum oxide (Al2O3). After coating, the cycle stability of the material is significantly improved, and the capacity retention rate can still reach 85% after 500 cycles.

[0111] Example 2: Preparation and performance study of titanium-doped lithium iron phosphate positive electrode material

[0112] In this embodiment, the positive electrode material is titanium-doped lithium iron phosphate (LiFePO 4 ), and the electronic conductivity and ion diffusion of the material are improved by doping with titanium ions (Ti 4 + ).

[0113] 2.1 Material synthesis:

[0114] The LiFe0.98Ti0.02PO4 cathode material was prepared by solid phase reaction method. First, Li2CO3, FePO4 and TiO2 were weighed as precursors according to the stoichiometric ratio and mixed evenly. Then, the mixture was heated to 700℃ and calcined for 10 hours under nitrogen atmosphere to obtain the target material.

[0115] 2.2 Structural characterization:

[0116] X-ray photoelectron spectroscopy (XPS) analysis found that the doped titanium ions were mainly located at the Fe site of the material lattice. The microstructure of the material was observed by transmission electron microscopy (TEM), and the results showed that the crystal structure of the doped material remained intact, and the particle size was relatively uniform, about 100 nanometers.

[0117] 2.3 Electrochemical performance test:

[0118] By assembling into button cells and conducting cyclic voltammetry (CV) tests, the results showed that the initial discharge capacity of titanium-doped LiFePO4 at 1C rate was 150mAh / g, and the capacity retention rate was 95% after 300 cycles. In addition, EIS tests showed that after titanium doping, the ion diffusion impedance of the material was significantly reduced, improving the high-rate charge and discharge performance.

[0119] 2.4 Electrolyte compatibility study:

[0120] Further research on the compatibility of titanium-doped LiFePO4 materials in different electrolytes revealed that the interfacial reaction between the material and LiPF6 solution was relatively stable, which could effectively reduce the internal resistance of the battery and further improve the cycle life and safety performance of the battery.

[0121] These two examples demonstrate the optimization strategy of achieving high-performance lithium-ion battery cathode materials through different doping elements (such as magnesium and titanium) and surface modification methods (such as alumina coating). Each example significantly improves the electrochemical performance and cycle stability of the material by precisely controlling the microstructure and surface characteristics of the material.

[0122] The following are four specific application examples, which target different formulations and preparation conditions of high-performance lithium-ion battery positive electrode materials, and demonstrate the doping elements, preparation processes, and performance enhancement effects of the materials.

[0123] Application Example 1: Preparation of magnesium-doped lithium nickel cobalt manganese oxide (lithium nickel cobalt manganese oxide) positive electrode material

[0124] 1. Material formula: nickel cobalt lithium manganese oxide matrix material, magnesium (Mg) doping amount is 1.0wt%.

[0125] 2. Preparation process: Co-precipitation method is adopted. Nitrate of nickel, cobalt and manganese is dissolved in deionized water, and an appropriate amount of magnesium hydroxide is added to control the pH value to about 10 to form a precipitate. After drying, calcination is carried out at 800°C for 10 hours.

[0126] 3. Microstructure: A hexagonal α-NaFeO_2 type crystal structure with an average particle diameter of 800nm ​​was obtained, and the particle surface had a certain porosity.

[0127] 4. Performance test: The initial specific capacity of this material reaches 170 mAh / g, and the capacity retention rate exceeds 92% after 100 cycles at a rate of 0.5C, showing excellent cycle stability and rate performance.

[0128] Application Example 2: Preparation of magnesium-aluminum doped lithium nickel cobalt manganese oxide (lithium nickel cobalt manganese oxide) positive electrode material

[0129] 1. Material formula: lithium nickel cobalt manganese oxide matrix material, magnesium (Mg) and aluminum (Al) doping amounts are 0.5wt% and 1.0wt% respectively.

[0130] 2. Preparation process: Sol-gel method is adopted. Nitrates of nickel, cobalt, manganese, magnesium and aluminum are dissolved and citric acid is added as a complexing agent, and the sol reaction is carried out at 80°C. After drying, the sol reaction is carried out at 850°C for 12 hours.

[0131] 3. Microstructure: The obtained particles have a particle size of 700 nm and a hexagonal α-NaFeO_2 crystal structure with a higher specific surface area.

[0132] 4. Performance test: The specific capacity is 175 mAh / g, and the capacity retention rate is 90% after 200 cycles at a 1C rate. The capacity retention rate at high temperature is significantly better than that of the undoped sample, showing good thermal stability.

[0133] Application Example 3: Preparation of magnesium-aluminum-titanium doped nickel-cobalt-manganese oxide (nickel-cobalt-manganese oxide) positive electrode material

[0134] 1. Material formula: lithium nickel cobalt manganese oxide matrix material, magnesium (Mg), aluminum (Al) and titanium (Ti) doping amounts are 1.0wt%, 0.5wt% and 0.5wt% respectively.

[0135] 2. Preparation process: Solid phase sintering method is adopted. Nickel, cobalt, manganese, magnesium, aluminum and titanium oxides are mixed in proportion, ground evenly and pre-fired at 750℃, and then cooled and ground and calcined at 850℃ for 10 hours.

[0136] 3. Microstructure: Forming a cathode material with nano-scale particles with moderate porosity to form a short ion diffusion path.

[0137] 4. Performance test: The specific capacity of the material is 180mAh / g, and the capacity retention rate is 85% after 500 cycles at 5C rate. It can still maintain stable cycle performance under high rate conditions.

[0138] Application Example 4: Preparation of Aluminum-Titanium Doped Nickel-Cobalt-Manganese Oxide (NiCoMnO4) Positive Electrode Material

[0139] 1. Material formula: lithium nickel cobalt manganese oxide matrix material, aluminum (Al) and titanium (Ti) doping amounts are 1.0wt% and 1.0wt% respectively.

[0140] 2. Preparation process: Co-precipitation method combined with high temperature solid phase method is adopted. After the nitrates of nickel, cobalt, manganese, aluminum and titanium are dissolved, the pH value is controlled to be 11 at 80°C to form a precipitate, which is then dried and ground and calcined at 900°C for 12 hours.

[0141] 3. Microstructure: The particle surface is smooth, the particle size is in the range of 500-1000nm, the crystal structure is a stable α-NaFeO_2 type, and it presents a uniform micropore distribution.

[0142] 4. Performance test: The initial specific capacity reaches 185mAh / g, and the capacity retention rate is 88% after 300 cycles at 2C rate. The performance is stable in high temperature (60°C) environment and is suitable for high temperature and high rate applications.

[0143] These four examples demonstrate the effects of different combinations of doping elements on improving material performance, including capacity, rate performance, thermal stability, and cycle life.

[0144] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A high-performance lithium-ion battery positive electrode material, characterized in that: The positive electrode material is a porous structure material with a nickel cobalt lithium manganese oxide matrix. The material is prepared by a sol-gel method and is doped with magnesium, aluminum, and titanium elements. The concentration of the doped elements is controlled at 0.5-2.0wt%; the material has a hexagonal α-NaFeO_2 crystal structure, the particle size is controlled in the range of 500nm to 1.5μm, and the particle morphology is a porous spherical structure.

2. The high performance lithium ion battery positive electrode material according to claim 1, characterized in that: The material uses a new combination of doping elements, including magnesium, aluminum, titanium metal or non-metallic ions. By adjusting the type, concentration and distribution of the doping ions, the electronic structure and crystal structure of the material can be precisely controlled, thereby improving the material's electronic conductivity, ion diffusion performance and high-rate electrochemical performance. Doping also enhances the thermal stability of the material and reduces capacity attenuation under high temperature conditions.

3. The high performance lithium ion battery positive electrode material according to claim 1, characterized in that: The positive electrode material is a magnesium, aluminum and titanium doped nickel cobalt manganese oxide material. By evenly distributing magnesium, aluminum and titanium in the lattice at a doping amount of 0.5-2.0%, the electronic structure and crystal structure are regulated to enhance the electronic conductivity, ion diffusion performance and high-rate electrochemical performance of the material; the doping structure also improves the thermal stability of the material in a high temperature environment and reduces the capacity decay rate.

4. The high performance lithium ion battery positive electrode material according to claim 1, characterized in that: The preparation method of the material includes a sol-gel method, and the specific steps are: Precursors of nickel, cobalt, manganese, magnesium, aluminum and titanium are mixed and dissolved in proportion to form a uniform solution; Adding a complexing agent and performing a sol reaction to obtain a uniformly distributed sol; The final magnesium-aluminum-titanium doped lithium nickel-cobalt-manganese oxide material is obtained after drying and calcination to ensure that the doping elements are evenly distributed and form a stable crystal structure.

5. The high performance lithium ion battery positive electrode material according to claim 1, characterized in that: The microstructure of the material is a porous structure with a particle diameter of 500nm to 1.5μm, has a large specific surface area, and a hexagonal α-NaFeO_2 crystal structure. The morphology and porosity of the particles are controlled by optimizing the synthesis process to shorten the diffusion path of lithium ions in the positive electrode material, thereby improving the rate performance and cycle stability of the material.

6. A method for preparing a high-performance lithium-ion battery positive electrode material, characterized in that: A method for preparing a high-performance lithium-ion battery positive electrode material, specifically comprising: S1: Material synthesis, using a variety of synthesis methods, such as solid phase reaction method, sol-gel method, hydrothermal method, etc., to prepare the target positive electrode material; S2: Structural characterization, using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and other methods to characterize the crystal structure, microscopic morphology, element valence state, etc. of the synthesized materials in detail; S3: Electrochemical performance test, through constant current charge and discharge test, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and other methods, to evaluate the electrochemical properties of the positive electrode material, such as specific capacity, cycle performance, and rate performance; S4: Surface modification and coating research, exploring the effect of surface coating materials (such as carbon layer, oxide layer, etc.) on the stability and electrochemical performance of positive electrode materials, and studying the effects of different coating methods and coating amounts on performance; S5: The effect of ion doping on performance. Introduce different ions (such as magnesium, aluminum, titanium, etc.) for doping to improve the electronic conductivity and ion diffusion properties of the material. Study the influence of the type, concentration and distribution of doped ions on the performance of the positive electrode material. S6: Compatibility study with electrolyte, examine the electrochemical behavior of cathode materials in different electrolyte systems, optimize electrolyte formulation to improve battery performance, and study the interface reaction mechanism between cathode materials and electrolyte.

7. The method for preparing a high-performance lithium-ion battery positive electrode material according to claim 6, characterized in that: Said S1 comprises: S11: weigh the raw materials according to the stoichiometric ratio and mix them thoroughly; S12: According to the selected synthesis method, controlling the reaction conditions (such as temperature, time, atmosphere, etc.) to perform the synthesis reaction; S13: washing, drying, grinding and other post-processing of the synthesized product.

8. The method for preparing a high-performance lithium-ion battery positive electrode material according to claim 6, characterized in that: The S2 comprises: S21: Determine the crystal structure and phase purity of the material using XRD; S22: Observe the microstructure and particle size of the material by SEM and TEM; S23: Use XPS to analyze the chemical state of elements on the surface of the material.

9. The method for preparing a high-performance lithium-ion battery positive electrode material according to claim 6, characterized in that: The S3 includes: S31: preparing positive electrode sheets and assembling them into button cells or soft pack batteries; S32: Perform constant current charge and discharge test under a certain voltage range and current density; S33: Perform CV and EIS tests to analyze electrode reaction kinetics and interface characteristics.